Spatial variability in water strontium isotopes and trace metals from the Clarence River Basin, New South Wales, Australia - Lauren J. Stoot; Lee J. Baumgartner; Gavin L. Butler; Jason D. Thiem; Brett M. Knowles; Gregory S. Doran (Hydrobiologia, 2024)
Understanding fish movement in river systems is essential in identifying habitats which are important for species to perpetuate. Water chemistry, paired with fish otoliths, can be used to trace movements among different habitats, although a detailed understanding of spatial variation in water chemistry is first required. To obtain this knowledge, we analysed surface water collected from 59 sites throughout the Clarence River Basin, a coastal river basin in northern New South Wales, Australia. The primary objective was to quantify the spatial variation of trace metals and strontium isotope ratios ( 87 Sr: 86 Sr) for future and paired use with otolith microchemistry to track fish movement. Using ICP-OES, we identified that some trace metals, particularly strontium and barium as well as 87 Sr: 86 Sr ratios, varied spatially when analysing all water samples and revealed three distinct regions centring around the estuary, interior and outer regions. These differences were driven by variation in the underlying surface geology between the Clarence–Moreton Basin and the New England Block. Tidal influence also affected trace metals and 87 Sr: 86 Sr ratios throughout the estuarine area. We suggest that the level of differentiation identified in the current study has the potential to discriminate broad-scale fish movements among regions/habitats using otolith analysis, with fine scale movements best elucidated using complementary techniques.